2018
DOI: 10.1080/00015458.2018.1515338
|View full text |Cite
|
Sign up to set email alerts
|

Low Hartmann’s procedure or intersphincteric abdominoperineal resection in the primary treatment of low rectal cancer; a survey among surgeons evaluating current practice

Abstract: Background: Low Hartmann's procedure (LHP) and intersphincteric abdominoperineal resection (iAPR) are both surgical options in the treatment of distal rectal cancer when there is no intention to restore bowel continuity. This study aimed to evaluate current practice among members of the Dutch Association of Coloproctology (WCP). Methods: An online survey among members of the WCP who represent 66 Dutch hospitals was conducted. The survey consisted of 15 questions addressing indications for surgical procedures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The choice between LH and ISAPR is ultimately dependent on the surgeon preference and comfort with the procedure in question has a large impact on the choice. A recent Dutch survey found that 86% of surgeons preferred ISAPR to LH, demonstrating a significant shift in preferences compared to a similar study 5 years earlier 22 . While no reasons where given for this change, it is likely that the recent reports of favourable outcomes following ISAPR contributed to this.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The choice between LH and ISAPR is ultimately dependent on the surgeon preference and comfort with the procedure in question has a large impact on the choice. A recent Dutch survey found that 86% of surgeons preferred ISAPR to LH, demonstrating a significant shift in preferences compared to a similar study 5 years earlier 22 . While no reasons where given for this change, it is likely that the recent reports of favourable outcomes following ISAPR contributed to this.…”
Section: Discussionmentioning
confidence: 92%
“…A recent Dutch survey found that 86% of surgeons preferred ISAPR to LH, demonstrating a significant shift in preferences compared to a similar study 5 years earlier. 22 While no reasons where given for this change, it is likely that the recent reports of favourable outcomes following ISAPR contributed to this.…”
Section: Discussionmentioning
confidence: 99%
“…In this UK cohort there was a tendency for surgeons to perform HP rather than IAPE. This is in contrast to European units where IAPE is the preferred technique in this setting [11]. The reasons for avoiding an anastomosis were as expected: the risk of pelvic sepsis from an anastomotic leak, concerns over poor function and/or frailty.…”
Section: Discussionmentioning
confidence: 92%
“…There have been no prospective comparisons of the two procedures and no data on patient‐reported outcomes, which may be much more important than perceived morbidity. A recent survey of Dutch colorectal surgeons supported the perception that HP was associated with an unacceptably high rate of pelvic abscess and that IAPE should be the preferred procedure in this setting [11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to distal rectum closure and proximal endo-colostomy, it was traditionally regarded as one safer procedure and was often performed for those with a poor physical condition. It was associated with less surgical trauma and faster recovery [ 5 ]. In recent years, the term “low Hartmann’s procedure (LHP)” has been proposed, and it mainly refers to the procedure for tumors located within 10 cm of the anal verge [ 6 ].…”
Section: Introductionmentioning
confidence: 99%